2022
DOI: 10.1111/ane.13628
|View full text |Cite
|
Sign up to set email alerts
|

Blood biomarkers for Alzheimer's disease and related disorders

Abstract: Alzheimer's disease (AD) is a progressive neurodegenerative dementia for which disease-modifying treatments, likely to be the most effective in early disease stages (or even in primary prevention settings), are now being developed at a rapid pace. AD-related pathologies, key amongst which are extracellular amyloid β plaques, intra-neuronal tau tangles and neurodegeneration, are evident in the

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
30
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 45 publications
(93 reference statements)
0
30
0
Order By: Relevance
“…Very recent evidence indicates that up to ∼45% of all COVID-19 patients develop a mild-to-severe encephalopathy and encephalitis due to complications arising from viral-induced cytokine storm, elevated inflammatory signaling and/or antineural autoimmunity, sometimes referred to as a "cytokine storm syndrome" (Mao et al, 2020;Vigasova et al, 2021;Piekut et al, 2022). Just as is consistently observed in AD, the pro-inflammatory cytokines interleukin-1beta (IL-1β), IL-8, IL-1RA and IL-18 and serum neurofilament light (NF-L) chain protein in patient CSF and blood serum, biomarkers for all-cause inflammatory neurodegeneration are significantly associated with COVID-19 severity, and patients with AD appear to be associated with more severe complications of COVID-19 including increased morbidity and mortality (Mao et al, 2020;Krey et al, 2021;Chung et al, 2022;Guasp et al, 2022;Zetterberg and Schott, 2022).…”
Section: Sars-cov-2 Ad and Increased Susceptibility To Covid-19mentioning
confidence: 91%
“…Very recent evidence indicates that up to ∼45% of all COVID-19 patients develop a mild-to-severe encephalopathy and encephalitis due to complications arising from viral-induced cytokine storm, elevated inflammatory signaling and/or antineural autoimmunity, sometimes referred to as a "cytokine storm syndrome" (Mao et al, 2020;Vigasova et al, 2021;Piekut et al, 2022). Just as is consistently observed in AD, the pro-inflammatory cytokines interleukin-1beta (IL-1β), IL-8, IL-1RA and IL-18 and serum neurofilament light (NF-L) chain protein in patient CSF and blood serum, biomarkers for all-cause inflammatory neurodegeneration are significantly associated with COVID-19 severity, and patients with AD appear to be associated with more severe complications of COVID-19 including increased morbidity and mortality (Mao et al, 2020;Krey et al, 2021;Chung et al, 2022;Guasp et al, 2022;Zetterberg and Schott, 2022).…”
Section: Sars-cov-2 Ad and Increased Susceptibility To Covid-19mentioning
confidence: 91%
“…In addition, ideal biomarkers should benefit from being less invasive and fast to measure, providing results in minutes or hours, rather than days or weeks. Therefore, many biomarkers are explored in blood, saliva, or urine samples, as well as in imaging techniques including magnetic resonance or positron emission tomography (PET) ( Young et al, 2020 ; Zetterberg and Schott, 2022 ). In fact, live imaging of brain metabolism is currently proposed as an interesting biomarker method both in preclinical and clinical settings ( Zhu et al, 2018 ).…”
Section: Taurine As a Therapeutic Alternative In Nervous System Patho...mentioning
confidence: 99%
“…For example, Liang et al collected transcriptomic data coming from post-mortem brain tissue and identified region-specific gene expression alterations in AD brains 19 . In this study, we decided to pursue a blood-based gene expression analysis since the identification of a blood-based diagnostic signature could be extremely useful for pre-screening ahead of invasive and costly follow-up analysis 20 22 . Indeed, blood-based biomarkers represent an ideal option as the first-step of the diagnostic process beginning in primary care settings, and may help to determine which individuals should receive a referral to assessment by specialists, including CSF analysis, MRI or amyloid PET diagnostics.…”
Section: Introductionmentioning
confidence: 99%